Factors influencing Bumiputera contractors' acceptance of the contractor's all risk takāful product - Mohd Azizi Ibrahim; Alias Bin Mat Nor; Raja Rizal Iskandar Raja Hisham (ISRA International Journal of Islamic Finance, 2021)
Purpose - This research aims to investigate the factors that can influence Bumiputera contractors' acceptance of the Contractor's All Risks (CAR) takāful (Islamic insurance) product using the theory of reasoned action (TRA). Design/methodology/approach - Using the method of quantitative surveys, 414 questionnaires were collected from targeted Bumiputera contractors in Malaysia (grade G1 to grade G7), except in Sabah and Sarawak, that are registered with the Construction Industry Development Board (CIDB) and are also members of Persatuan Kontraktor Melayu Malaysia (PKMM). The data was analysed using the partial least squares structural equation modeling (PLS-SEM) technique. Findings - The findings from the PLS-SEM analysis show that attitude, subjective norm, religiosity and awareness have a positive relationship with Bumiputera contractors' acceptance of the CAR takāful product. Religiosity appeared to be the most significant factor influencing Bumiputera contractors' acceptance of the CAR takāful product. Research limitations/implications - The respondents in this study only comprised Bumiputera contractors in Peninsular Malaysia, excluding those from Sabah and Sarawak. Therefore, it is not possible to generalise the findings to a broader population. Practical implications - Takāful operators and their sales and marketing departments need to act proactively in promoting the benefits of investing in CAR takāful that follows Sharīʾah (Islamic law) rules and principles. They should create mechanisms to market CAR takāful better, thus accelerating its acceptance rate among contractors. Originality/value - The paper uses the proposed extended TRA model, which includes the variables of religiosity and awareness in the TRA model. These variables were successfully integrated in the model, and the findings show that they have significantly contributed to the acceptance of the CAR takāful product among Bumiputera contractors.
Keywords: 330; Attitude; Awareness; CAR Takāful; Religiosity; Subjective norm; Theory of reasoned action (TRA)